ONA TILI VA ADABIYOT DARSLARIDA GURUHLI LOYIHA ISHLARINING O‘QUVCHILAR FAOLLIGIGA TA’SIRI (International conference on multidisciplinary science, 2026)
The article theoretically analyzes the impact of group project work on student activity in native language and literature classes. Based on Johnson and Johnson's cooperative learning theory, Dale's "cone of experience" model, and Tuckman's theory of group development stages, the mechanisms of increasing student activity in group project work are studied. Comparative analysis clearly showed the differences between individual assignments and group project work in 5 elements of cooperative learning. The results of the study theoretically substantiate the fact that group project work has a significant advantage over individual assignments in increasing student activity.